Evaluasi Pembelajaran Pada Mata Kuliah Pengantar Ushul Fiqih dalam Perspektif Mahasiswa - Siti Sahra; Radino Radino; Mahmud Arif; Retno Try Purnawati; Eko Swanto (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to examine students' perceptions of learning evaluation in the Introduction to Ushul Fiqih course at UIN Sunan Kalijaga Yogyakarta, focusing on the forms of evaluation, its effectiveness and relevance, and the factors shaping students' perceptions. While previous studies have largely examined student perceptions of technology-based evaluation media, this study looks at a course that requires conceptual and interpretive reasoning in Islamic law. Methods – This research uses a qualitative descriptive approach. The subjects were 10 students selected purposively from Classes A, C, and D. Data were collected through semi-structured interviews, non-participatory observation, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña, and data validity was checked through source and technique triangulation, member checking, and discussion with the research supervisor. Findings – The results show that students have a positive perception of the resume assignment as the main form of evaluation in the midterm exam, as it helps reinforce their conceptual understanding and produces notes they can use later. Even so, students feel this format is not enough to measure analytical and applicative skills, so they suggested other formats such as oral presentations, case studies, and formative quizzes. Students' perceptions are also shaped by internal factors, external factors, and the classroom environment.Research Implications – These findings suggest that evaluation in conceptually demanding courses like Ushul Fiqih needs to go beyond reproduction-based tasks and move toward authentic assessment principles and the CIPP model, particularly by strengthening the input and process dimensions through ongoing formative assessment.